(untitled) (SAINTEKBU, 2021)
Selection of ongoing bidikmisi scholarship recipients for K.H. A. Wahab Hasbullah is still done manually. In practice, the leadership and organizing officers still find it difficult to determine the candidates for bidikmisi scholarship recipients because the number of applicants is not proportional to the quota provided by DIKTI for bidikmisi recipients. The large number of required documents to apply for Bidikmisi scholarships also cre-ates problems for selection organizers, especially in terms of data management requirements. To make it easier for leaders and administering officers, a decision support system is needed, which is known as a data manage-ment system to make it easier for the selection process for bidikmisi on-going recipients. A decision support system is a specific information system aimed at assisting management in making decisions related to solve semi-structured problems. In this study, the decision-making process for selection of ongoing bidikmisi scholar-ship recipients uses the SAW method. The SAW method was chosen because it was able to complete the best alternative from a number of alternative solutions and had the basic concept of looking for a weighted sum of the performance of each alternative on all attributes, so that it could be used in various types of criteria that researchers would use in accordance with the criteria for the recipient of Bidikmisi on Going on the Bidikmisi official website.